On lunar exospheric column densities and solar wind access beyond the terminator from ROSAT soft X‐ray observations of solar wind charge exchange. Issue 7 (3rd July 2014) - Collier, Michael R.; Snowden, S. L.; Sarantos, M.; Benna, M.; Carter, J. A.; Cravens, T. E.; Farrell, W. M.; Fatemi, S.; Hills, H. Kent; Hodges, R. R.; Holmström, M.; Kuntz, K. D.; et al.
Abstract We analyze the Röntgen satellite (ROSAT) position sensitive proportional counter soft X‐ray image of the Moon taken on 29 June 1990 by examining the radial profile of the surface brightness in three wedges: two 19° wedges (one north and one south) 13–32° off the terminator toward the dark side and one wedge 38° wide centered on the antisolar direction. The radial profiles of both the north and the south wedges show significant limb brightening that is absent in the 38° wide antisolar wedge. An analysis of the soft X‐ray intensity increase associated with the limb brightening shows that its magnitude is consistent with that expected due to solar wind charge exchange (SWCX) with the tenuous lunar atmosphere based on lunar exospheric models and hybrid simulation results of solar wind access beyond the terminator. Soft X‐ray imaging thus can independently infer the total lunar limb column density including all species, a property that before now has not been measured, and provide a large‐scale picture of the solar wind‐lunar interaction. Because the SWCX signal appears to be dominated by exospheric species arising from solar wind implantation, this technique can also determine how the exosphere varies with solar wind conditions. Now, along with Mars, Venus, and Earth, the Moon represents another solar system body at which SWCX has been observed.